Transcription factor Tbx3 is required for the specification of the atrioventricular conduction system. - Bakker, M; Boukens, B; Mommersteeg, M; Brons, J; Wakker, V; Moorman, A; Christoffels, V (2008)
The cardiac conduction system consists of distinctive heart muscle cells that initiate and propagate the electric impulse required for coordinated contraction. The conduction system expresses the transcriptional repressor Tbx3, which is required for vertebrate development and controls the formation of the sinus node. In humans, mutations in Tbx3 cause ulnar-mammary syndrome. Here, we investigated the role of Tbx3 in the molecular specification of the atrioventricular conduction system. Expression analysis revealed early delineation of the atrioventricular bundle and proximal bundle branches by Tbx3 expression in human, mouse, and chicken. Tbx3-deficient mice, which die between embryonic day 12.5 and 15.5, ectopically expressed genes for connexin (Cx)43, atrial natriuretic factor (Nppa), Tbx18, and Tbx20 in the atrioventricular bundle and proximal bundle branches. Cx40 was precociously upregulated in the atrioventricular bundle of Tbx3 mutants. Moreover, the atrioventricular bundle and branches failed to exit the cell cycle in Tbx3 mutant embryos. Finally, Tbx3-deficient embryos developed outflow tract malformations and ventricular septal defects. These data reveal that Tbx3 is required for the molecular specification of the atrioventricular bundle and bundle branches and for the development of the ventricular septum and outflow tract. Our data suggest a mechanism in which Tbx3 represses differentiation into ventricular working myocardium, thereby imposing the conduction system phenotype on cells within its expression domain.